Analisis Karakteristik Persebaran Pasar Informal Berdasarkan Hirarki Jalan di Kota Balikpapan - Nopriyanti, Nabilla; Syafitri, Elin Diyah; Dewanti, Ajeng Nugrahaning; Ulimaz, Mega (COMPACT: Spatial Development Journal, 2023)
Balikpapan City is one of the cities with a spatial planning concept oriented to the trade sector. Economic activity in the trade sector does not only focus on the formal sector but also includes the informal sector whose existence is very real in today's society. One phenomenon that shows the development of the informal sector is the movement of trading spaces that were supposed to be in people's markets, now moving closer to settlements and main city streets. This phenomenon also occurs in the city of Balikpapan. The purpose of this study was to determine the characteristics of informal market distribution in Balikpapan City. This study uses primary and secondary data with research methods in the form of scoring analysis, descriptive comparative analysis with overlay principles. The results of the study found that the characteristics of the distribution of informal markets in general in each road hierarchy are not having a business license, the market area is smaller than the formal market (existing conditions <700 m2), tends to be on the edge of the road, tends to be close to settlements and has non-permanent type buildings in the form of los or stalls. It was found that the informal market occurred because some traders could not afford to rent in the main market and were constrained by the distance to the main market, some traders also felt that the location outside the market was more strategic, and the location on the roadside tended to be close to residential areas and residences making it easier for traders to carry out trading activities. In terms of regional function, most of the informal market growth grows in trade and service areas, especially on primary arterial roads and secondary arteries, while a small part grows in residential, industrial and tourism areas.